2021
DOI: 10.1111/jfd.13360
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal transmission of Piscirickettsia salmonis from the wild sub‐Antarctic notothenioid fish Eleginops maclovinus to rainbow trout (Oncorhynchus mykiss) under experimental conditions

Abstract: Piscirickettsia salmonis is the aetiological agent of piscirickettsiosis, a bacterial disease that affects farmed salmonids, causing high mortalities and significant economic losses in the Chilean salmon farm industry. Given the Chilean native fish species Patagonian blenny, Eleginops maclovinus, lives in the vicinity of salmon farms, it is relevant to clarify the epidemiological role that this species could play in the transmission and/or dissemination of this pathogen. This study aimed to evaluate the bidire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…47 Pathogen-monitoring studies conducted between 2010 and 2018 in southern Chile established that of 7518 specimens of Patagonian blenny (Eleginops maclovinus), only 10.7% (i.e., n = 803) tested positive for P. salmonis through qPCR analysis. 49 Quintanilla et al 49 further reported the ability of P. salmonis to be transmitted from Patagonian blenny to rainbow trout through cohabitation. The susceptible trout presented pathological injuries consistent with piscirickettsiosis, and the inoculated agent was also isolated.…”
Section: The Role Of Piscirickettsiosis In Chilean Salmon Farmingmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Pathogen-monitoring studies conducted between 2010 and 2018 in southern Chile established that of 7518 specimens of Patagonian blenny (Eleginops maclovinus), only 10.7% (i.e., n = 803) tested positive for P. salmonis through qPCR analysis. 49 Quintanilla et al 49 further reported the ability of P. salmonis to be transmitted from Patagonian blenny to rainbow trout through cohabitation. The susceptible trout presented pathological injuries consistent with piscirickettsiosis, and the inoculated agent was also isolated.…”
Section: The Role Of Piscirickettsiosis In Chilean Salmon Farmingmentioning
confidence: 99%
“…Of the sampled specimens, only 3.45% tested positive for the detection of P. salmonis DNA 47 . Pathogen‐monitoring studies conducted between 2010 and 2018 in southern Chile established that of 7518 specimens of Patagonian blenny ( Eleginops maclovinus ), only 10.7% (i.e., n = 803) tested positive for P. salmonis through qPCR analysis 49 . Quintanilla et al 49 further reported the ability of P. salmonis to be transmitted from Patagonian blenny to rainbow trout through cohabitation.…”
Section: The Role Of Piscirickettsiosis In Chilean Salmon Farmingmentioning
confidence: 99%